Tumor necrosis factor alpha is a key modulator of inflammation in cerebral aneurysms - (:unkn) unknown (OXFORD UNIV PRESS INC, 2005)
OBJECTIVE: Although intracranial aneurysms (IAs) are a major public health problem in the United States, few etiological factors are known. Most aneurysms remain asymptomatic until they rupture, producing subarachnoid hemorrhage, one of the most severe forms of stroke. Despite the technical advances in endovascular and microsurgical treatment, these patients still have high mortality and morbidity rates. Hence, the biology of aneurysm formation and growth is of intense interest. The presence of T and B lymphocytes, as well as macrophages, in human IA tissues suggests a role for inflammation in IA pathogenesis. However, the types of cytokines that are involved and regulated during cerebral aneurysm formation and growth are not known. To study the underlying pathogenesis of IA, we analyzed the expression of cytokines that participate in proinflammatory and anti-inflammatory responses. METHODS: Polymerase chain reaction was used to assess relative messenger ribonucleic acid expression levels of cytokines and an apoptotic modulator, Fas-associated death domain protein. Western blot analysis was used to determine protein expression from these genes. RESULTS: We show that the proinflammatory cytokine, tumor necrosis factor a and its proapoptotic downstream target, Fas-associated death domain protein, are increased in human aneurysms. In contrast, interleukin 10, which is secreted predominantly by T helper 2 cells, was absent in aneurysms. Polymerase chain reaction-derived gene expression data were confirmed by Western blotting using specific antibodies. CONCLUSION: Increased tumor necrosis factor a and Fas-associated death domain protein may have deleterious primary and secondary effects on cerebral arteries by promoting inflammation and subsequent apoptosis in vascular and immune cells, thereby weakening vessel walls.
Keywords: aneurysm growth; apoptosis; cytokines; inflammation; signaling; INTRACRANIAL ANEURYSMS; SUBARACHNOID HEMORRHAGE; NATURAL-HISTORY; APOPTOSIS; ACTIVATION; EXPRESSION; RUPTURE; CALCIUM; GENES; DEATH